The macronuclear genome of the Antarctic psychrophilic marine ciliate Euplotes focardii reveals new insights on molecular cold adaptation - Mozzicafreddo M.; Pucciarelli S.; Swart E. C.; Piersanti A.; Emmerich C.; Migliorelli G.; Ballarini P.; Miceli C. (Scientific Reports, 2021)
The macronuclear (MAC) genomes of ciliates belonging to the genus Euplotes species are comprised of numerous small DNA molecules, nanochromosomes, each typically encoding a single gene. These genomes are responsible for all gene expression during vegetative cell growth. Here, we report the analysis of the MAC genome from the Antarctic psychrophile Euplotes focardii. Nanochromosomes containing bacterial sequences were not found, suggesting that phenomena of horizontal gene transfer did not occur recently, even though this ciliate species has a substantial associated bacterial consortium. As in other euplotid species, E. focardii MAC genes are characterized by a high frequency of translational frameshifting. Furthermore, in order to characterize differences that may be consequent to cold adaptation and defense to oxidative stress, the main constraints of the Antarctic marine microorganisms, we compared E. focardii MAC genome with those available from mesophilic Euplotes species. We focussed mainly on the comparison of tubulin, antioxidant enzymes and heat shock protein (HSP) 70 families, molecules which possess peculiar characteristic correlated with cold adaptation in E. focardii. We found that α-tubulin genes and those encoding SODs and CATs antioxidant enzymes are more numerous than in the mesophilic Euplotes species. Furthermore, the phylogenetic trees showed that these molecules are divergent in the Antarctic species. In contrast, there are fewer hsp70 genes in E. focardii compared to mesophilic Euplotes and these genes do not respond to thermal stress but only to oxidative stress. Our results suggest that molecular adaptation to cold and oxidative stress in the Antarctic environment may not only be due to particular amino acid substitutions but also due to duplication and divergence of paralogous genes.